Application of the Geographic Information System (GIS) in immunisation service delivery; its use in the 2017/2018 measles vaccination campaign in Nigeria. (17th November 2021) - Oteri, Joseph; Idi Hussaini, Mohammed; Bawa, Samuel; Ibizugbe, Samuel; Lambo, Kikelomo; Mogekwu, Fred; Wiwa, Owen; Seaman, Vincent; Kolbe-Booysen, Olivia; Braka, Fiona; Nsubuga, Peter; Shuaib, Faisal
Abstract: Background: As global effort is made towards measles elimination, the use of innovative technology to enhance planning for the campaign has become critical. GIS technology has been applied to track polio vaccination activities in Nigeria with encouraging outcomes. Despite numerous measles vaccination campaigns after the first catch up campaign in 2005, sub-optimal outcomes of previous measles supplemental immunization activities necessitated the use of innovative ideas to achieve better outcomes especially when planning for the 2017/2018 measles vaccination campaign. This led to the application of the use of the GIS technology for the Northern states in 2017/2018 campaign. This study is a report of what was achieved with the use of the GIS in the 2017/2018 measles vaccination campaign in Nigeria. Methods: GIS generated ward maps were used for the microplanning processes for the 2017/2018 measles vaccination campaign. These ward maps had estimates of the target population by settlements, the number and location of vaccination posts ensuring that a vaccination post is sited within one-kilometer radius of a settlement, and the number of teams needed to support the vaccination campaign as well as the catchment area and daily implementation plans. The ward microplans were verified by checking for accuracy and consistency of the target population, settlements, number of teams, vaccination posts and daily implementation work plans using a standard checklist. The ward maps were deployed into use for the measles vaccination campaign after the state team driven validation and verification by the National team (Government and Partners) Results: The Northern states that applied the GIS technology had a closer operational target population to that on the verified microplan than those of the non-GIS technology states. Greater than 90% of the ward maps had all that is expected in the maps - i.e settlements, target populations, and vaccination posts captured, except Kaduna, Katsina and Adamawa states. Of all enumeration areas sampled during the post-campaign survey in states with GIS ward maps, none had a zero-vaccination coverage of the surveyed children, with the exception of one in Borno state that had security issues. In the post campaign coverage survey, the percentage of responses that gave vaccination post being too far as a reason for non-vaccination of children in the Northern zones that used GIS generated ward maps was less than half the rate seen in the southern zones where the GIS microplanning was not used. Conclusion: The use of GIS-generated wards maps improved the quality of ward micro plans and optimized the placement of vaccination posts, resulting in a significant reduction in zero-dose clusters found during the post campaign coverage survey.